1979
DOI: 10.6028/nbs.ir.79-1713
|View full text |Cite
|
Sign up to set email alerts
|

Final report on the "BFIRESVersion 1" computer simulation of emergency egress behavior during fires :

Abstract: This report is the final product of a specific effort to develop and analyze a computer simulation of human egress behavior during fires. This project was one component of a research program undertaken jointly by the Department of Health, Education and Welfare, and the Center for Fire Research of the National Bureau of Standards. In addition to the behavior of institutionalized populations during fire situations, this program considered the problems of design analysis, fire and smoke detection, smoke movement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…• Partial Behavioral models: PEDROUTE/PAXPORT [26][27][28][29][30][31][32] , EXIT89 [33][34][35][36][37][38][39] , Simulex 40-47 , GridFlow 48 , and ALLSAFE 49-51 . • Behavioral models: CRISP [52][53][54][55] , ASERI [56][57][58][59] , BFIRES-2 [60][61][62] , buildingEXODUS 4,[63][64][65][66][67][68] , EGRESS [69][70][71] , EXITT 72,73 , VEgAS [74][75][76] , E-SCAPE 77 , BGRAF [78][79][80][81] , EvacSim 82,83 , Legion [84][85]…”
Section: Features Of Egress Modelsmentioning
confidence: 99%
“…• Partial Behavioral models: PEDROUTE/PAXPORT [26][27][28][29][30][31][32] , EXIT89 [33][34][35][36][37][38][39] , Simulex 40-47 , GridFlow 48 , and ALLSAFE 49-51 . • Behavioral models: CRISP [52][53][54][55] , ASERI [56][57][58][59] , BFIRES-2 [60][61][62] , buildingEXODUS 4,[63][64][65][66][67][68] , EGRESS [69][70][71] , EXITT 72,73 , VEgAS [74][75][76] , E-SCAPE 77 , BGRAF [78][79][80][81] , EvacSim 82,83 , Legion [84][85]…”
Section: Features Of Egress Modelsmentioning
confidence: 99%
“…During the course of the project an attempt was made to posit a model of emergency escape behavior, and to functionally relate provisions of the Code to such a model. Principal components of this time-based model included; sensation and perception of emergency environmental cues, interpretation of emergency cues, strategy formation and decisionmaking, action initiation, and action completion (generally after models suggested elsewhere by Bickman, Edelman and McDaniel, 1977;Stahl, 1978aStahl, , 1979Stahl, , 1980and others). However, organizations based upon a time-based model of human response were found incapable of accommodating numerous Important code provisions.…”
Section: Organization Of the Reportmentioning
confidence: 99%
“…The literature review revealed little substantive technical data directly relevant to this issue. Moreover, although a number of time-based models of emergency behavior have appeared in the literature (Bickman et al, 1977;Stahl, 1978aStahl, , 1979Stahl, , 1980), only Stahl's computer simulation model postulates specific mechanisms by which information about exits and egress paths is applied to strategy formation and evaluation. The review of pertinent technical literature which follows here covers the state-of-the-art.…”
Section: 33 Assessment Of Behavioral Assumptions Based On the Techmentioning
confidence: 99%
“…(3) Denotes point infiltrated by fire products. (4) Floor plan elements (e.g., walls) drawn-in by user. • (20) fN0EXP (20) This section addresses the BFIRES executive, which has been modified to process the smoke and rescue modules, and to facilitate the expanded input, output and utility features of BFIRES II.…”
Section: Subroutines Initlz Initfr and Cmputementioning
confidence: 99%